Groundwater Conservation and Global Food Security: An exploratory assessment - Singh, Vartika; Ringler, Claudia; Pérez, Nicostrato D. (Polytechnic University of Valencia, 2022)
Water and food security are intrinsically linked as agriculture accounts for 70% of global water withdrawals. To jointly achieve Sustainable Development Goal (SDG) 2 on zero hunger and SDG 6 on safe water and sanitation, halting groundwater depletion without compromising food security will be key. The study uses the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT)’s system of inter-linked models around a core of hydrology model and food-market model of global production, trade, demand, and prices for agricultural commodities. We analyze four alternative scenarios that aim to halt groundwater depletion without further compromising global food security. Our results suggest that impacts of GWC are largest in India, China, and the US, which are also the three globally largest groundwater depleting countries. We find that mitigation options such as groundwater conservation and investing in agricultural R&D, and reducing meat consumption can offset negative impacts, thereby ensuring food security of a larger share of the population.